PENGARUH BUDAYA ORGANISASI DAN ETIKA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) GURU SMA NEGERI DI SIPORA KABUPATEN KEPULAUAN MENTAWAI - MEIHEN JALISMEN (Universitas Negeri Jakarta, 2015)
This study aims to determine the direct effect between (1) organizational culture with OCB, (2) ethics with OCB, (3) organization culture with ethical. The method used is a survey method with a correlation approach. In this study serve as a sample of 81 teachers were selected based on random techniques (simple random sampling). Data were obtained by spreading questioner. This study was conducted in high schools in Sipora Mentawai Islands. Based on hypothesis testing that has been done, it can be described as the following research findings: (1) there is a positive direct influence of organizational culture with OCB, (2) there is a positive direct influence of ethics on OCB, (3) there is a positive direct influence between cultures organization with ethics.